Year Five Pupils’ Number Sense and Algebraic Thinking: the Mediating Role of Symbol and Pattern Sense - Piriya, Somasundram; Zamri, Sharifah Norul Akmar Syed; Leong, Kwan Eu (Adam Marszalek Publishing House, 2019)
This study mainly focused on the relationship between number sense and algebraic thinking. Previous studies have provided evidence that number sense plays an important role in developing algebraic thinking. The role of symbol and pattern sense are yet to discover in relation to number sense and algebraic thinking. The purpose of this study was to identify the mediating effects of symbol sense and pattern sense in year five pupils’ relationship between number sense and algebraic thinking. To do so, two mathematics tests were carried out among 720 year five pupils in the district of Malacca, Malaysia. The collected data were analysed using a partial least squares-struc-tural equation modeling approach. The data collected were analysed using SPSS 22.0 and SmartPLS 3.0. Results demonstrated that symbol sense and pattern sense are good mediators between year five pupils’ number sense and algebraic thinking. This result of this study supports the past studies related to the role of number sense, symbol and pattern sense in developing algebraic thinking. The presented study provides suggestions as intervention to increase students’ making sense ability in numbers, symbols and patterns to develop algebraic thinking. © 2019, Adam Marszalek Publishing House. All rights reserved.